Decongestive diuresis using combination intravenous loop diuretics plus chlorothiazide in type 1 acute cardiorenal syndrome and worsening acute kidney injury; a neglected paradigm in resource-poor settings - Macaulay Amechi Chukwukadibia Onuigbo (Society of Diabetic Nephropathy Prevention, 2020)
Over the last decade or more, there has grown a body of evidence demonstrating that renal dysfunction in heart failure is a combination of forward failure from reduced cardiac output and therefore reduced glomerular filtration rate, as well as "congestive renal failure" secondary to renal venous hypertension. We had demonstrated the efficacy of combination intravenous loop diuretics used concurrently with intravenous chlorothiazide to achieve significant renal salvage in such patients at the Mayo Clinic Health System in Northwestern Wisconsin. We describe a similar recent experience with three consecutive elderly patients at the University of Vermont Medical Center, Burlington, VT, USA. We posit that this paradigm of care is underutilized. We argue that aggressive decongestive therapy with combination intravenous loop and thiazide diuretics is a neglected and underutilized mechanism and must be utilized more frequently in the treatment of worsening renal failure with type 1 cardiorenal syndrome. This imperative is even most compelling in resource-poor settings where mechanical ultrafiltration with dialysis or similar machines is not available or simply not affordable. Moreover, we had also demonstrated that accelerated rising Pro B natriuretic peptide (Pro-BNP) in such patients portends a good prognosticator for renal salvage. We present here three consecutive elderly patients recently so managed successfully at the University of Vermont Medical Center in Burlington, VT, USA.